The effect of roots and easily available carbon on the decomposition of soil organic matter fractions in boreal forest soil. (July 2017) - Pumpanen, J.; Lindén, A.; Bruckman, V. J.; Berninger, F.; Ilvesniemi, H.; Oinonen, M.; Sonninen, E.; Kukumägi, M.; Heinonsalo, J.
Abstract : The priming effect induced by carbon (C) that is easily available to microbes has been shown to increase the mineralization of soil organic matter (SOM) that is resistant to decomposition, but the combined effects of easily available carbon and the living root system have rarely been studied. The aim of this research was to study the decomposition of SOM fractions of different solubility in water and their 13 C, 14 C and 15 N abundance with and without the presence of a living root system and easily available carbohydrate in the form of glucose. The SOM collected from the organic horizon of a boreal forest soil in Hyytiälä, southern Finland (61°51′N, 24°17′E), and exposed to laboratory incubations with and without the presence of Pinus sylvestris L. seedlings and glucose, was separated into three chemical fractions with accelerated solvent (ASE) and pressurized hot water extractions (PHWE). Changes in the natural abundance of 13 C, 14 C and 15 N, spectral properties assessed by Fourier transform infrared spectroscopy (FTIR) and the C and N pools of SOM fractions were studied after incubation for 6 months. The extractions separated SOM into fractions with distinctive isotopic composition. The most easily soluble SOM fraction showed the largest abundance of 15 N and 14 C, and the living root system induced changes in the abundance of 15 N and FTIR spectra. Our research suggests that plant roots may induce SOM degradation and N uptake from soluble SOM fractions, but 13 C, 14 C, 15 N or FTIR alone cannot be used to describe the recalcitrance of SOM and its accessibility to microorganisms. It is better to use several methods in parallel to study the decomposability of SOM. Highlights: We studied the effects of tree roots and addition of glucose on the solubility of soil organic matter (SOM). SOM can be separated into pools with distinctive isotopic concentrations with pressurized hot water. Roots may induce organic matter degradation and N uptake from soluble SOM fractions. Larger 14 C abundance in soluble SOM indicated it contained older C than the recently assimilated C.